What This River Keeps : A Novel - Schwipps, Greg (Book collections on Project MUSE., 2012)
In the rolling hills of southern Indiana, an elderly couple copes with the fear that their river bottom farm-- the only home they've ever known-- will be taken from them through an act of eminent domain so the river flowing through their land may be dammed to form a reservoir. Their son sinks deeper into troubles of his own, struggling to determine his place in a new romantic relationship and the duty he owes to his family's legacy.